Precise somatotopic thalamocortical axon guidance depends on LPA-mediated PRG-2/radixin signaling - Cheng, J; Sahani, S; Hausrat, T; Yang, J; Ji, H; Schmarowski, N; Endle, H; Liu, X; Li, Y; Böttche, R; Radyushkin, K; Maric, H; et al. (Cell Press, 2016)
Precise connection of thalamic barreloids with their corresponding cortical barrels is critical for processing of vibrissal sensory information. Here, we show that PRG-2, a phospholipid-interacting molecule, is important for thalamocortical axon guidance. Developing thalamocortical fibers both in PRG-2 full knockout (KO) and in thalamus-specific KO mice prematurely entered the cortical plate, eventually innervating non-corresponding barrels. This misrouting relied on lost axonal sensitivity toward lysophosphatidic acid (LPA), which failed to repel PRG-2-deficient thalamocortical fibers. PRG-2 electroporation in the PRG-2(-/-) thalamus restored the aberrant cortical innervation. We identified radixin as a PRG-2 interaction partner and showed that radixin accumulation in growth cones and its LPA-dependent phosphorylation depend on its binding to specific regions within the C-terminal region of PRG-2. In vivo recordings and whisker-specific behavioral tests demonstrated sensory discrimination deficits in PRG-2(-/-) animals. Our data show that bioactive phospholipids and PRG-2 are critical for guiding thalamic axons to their proper cortical targets.